Investment Strategies in Emerging New Trends in Finance - Gharoie Ahangar, Reza; Salman, Asma (IntechOpen, 2021)
Investment and portfolio strategies are some of the most exciting topics in finance. This book presents the most up-to-date topics and techniques in finance to facilitate the investment process for researchers and investors in selecting appropriate investment strategies with the emergence of new issues and concepts in financial areas. This book contains nine chapters divided into three sections: The first section, "Investment and Portfolio Strategies," discusses different investment strategies in portfolio selection. The second section, "Behavioral Finance and Investment Decisions," examines the application of behavioral finance in investment decisions. The last section, "Emerging New Trends in Finance," includes some new and interesting finance topics that can depict our vision for the future arena of finance.